Ramescência do arco aortico no gambá-de-orelha-branca (Didelphis albiventris) - Schimming, Bruno Cesar [UNESP]; de Jesus, Luan Sabino Barroso Silva; Filadelpho, André Luis [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2016)
Knowledge of the aortic arch main and collateral branches is important because these arteries supply vital organs found in the head, neck, thoracic cavity and forelimbs of domestic and wild animals. This study aimed to contribute to the anatomical knowledge in opossums and collaborate with veterinary medical and surgical clinics. Thus, the anatomy of aortic arch was described in eighteen opossums. The results indicated that the aortic arch gives off the brachiocephalic trunk and the left subclavian artery in all animals studied. The branching pattern of the aortic arch is similar to that reported in the guinea pig, chinchilla, paca, raccoon, nutria, red squirrel, and ocelot. The brachiocephalic trunk showed as collateral branches, the right subclavian artery and the bicarotid trunk, that originated in the right and left common carotid arteries (77.7%). Bicarotid trunk was absent in four animals (22.2%). The right and left subclavian arteries originated in the vertebral artery, costocervical trunk, internal thoracic artery, and superficial cervical artery. Collateral branches of the subclavian artery showed similarities to that observed in other wild animals such as paca, ocelot and rock cavy.
Branching pattern of aortic arch in the white-eared opossum (Didelphis albiventris)
Keywords: Aorta artery; Heart; Marsupial; Opossum; Wildlife